Iron(III) Chloride Promoted Desulfitative C–C Coupling Reaction of α-Oxo Ketene Dithioacetals and Indoles: Highly Selective Synthesis of β,β-Bisindolyl and β-Indolyl α,β-Unsaturated Carbonyl Compounds - Yu, Haifeng; Li, Tiechun; Liao, Peiqiu (Synthesis, 2012)
The iron(III) chloride promoted desulfitative C–C coupling of α-oxo ketene dithioacetals with indoles was developed for the synthesis of indole derivatives. In the presence of iron(III) chloride, α-oxo ketene dithioacetals reacted efficiently and highly selectively with C2-unsubstituted or C2-substituted indoles to afford excellent yields of β,β-bisindolyl or β-indolyl α,β-unsaturated carbonyl compounds, respectively.
Keywords: heterocycles; coupling; indoles; desulfurizations; catalysis